Application of electronic invoicing and its accounting, tax and financial impact on motorbike sales companies in Huánuco - Figueredo-Morales, Franklin Z. (2023)
Objectives. The study sought to verify how the application of electronic invoicing affects the accounting, tax and financial aspects in companies selling motorbikes and spare parts in Huánuco. Methods. An observational study was carried out. The population consisted of 50 workers from 10 companies in the sector. A questionnaire, validated by experts, was used to evaluate the workers' opinion. Results. The sample consisted of 44 workers. 84% of them consider that electronic invoicing has improved the accounting, tax and financial aspects of their company and 89% consider that electronic invoicing correctly presents the financial situation of their company. Conclusion. Companies that apply electronic invoicing see benefits in accounting, tax and financial aspects.